Evaluation of the long-term memory T cell in mice after immunization with a live tularemia vaccine - A. S. Kartseva; M. V. Silkina; G. M. Titareva; T. I. Kombarova; R. I. Mironova; V. V. Firstova (Медицинская иммунология)
The vaccine strain F. tularensis 15 NIIEG induces long-lived cell-mediated immunity but exhibits a certain reactogenicity and genetic instability. Progress in development of a vaccine against tularemia has been limited by a lack of information regarding the mechanisms required to protect against this disease. The BALB/c mouse is the most commonly used animal to study tularemia due to its relatively low cost, well-characterized genetics, available immunological tools and mouse infection with virulent F. tularensis recapitulates human disease.CD4+ and CD8+T cells are known to be critical for the formation of protective immunity but the relative roles of memory T cell subpopulations in long lived protection against virulent strains of F. tularensis are not well established. We hypothesized that this immunity depends on central (TCM) and effector memory (TEM) T cells and their functional activity. In this study we have dissected the T cell immune response in BALB/c mice 30, 60 and 90 days after subcutaneous vaccination with 15 NIIEG.Multiparametric flow cytometry were used to characterize in vitro recall responses of splenocytes to F. tularensis antigen. TEM cells were identified as CD3+CD4+CD44+CD62L- and CD3+CD8+CD44+CD62L-, TCM cells as CD3+CD4+CD44+CD62L+ and CD3+CD8+CD44+CD62L+, respectively. The functional activity of memory T cells was assessed by the following parameters: the level of expression of the activation marker CD69 and cytokine-producing activity by staining with the intracellular cytokines IFNg and TNFa.Thus, development of a long-lived vaccine directed against F. tularensis is dependent on identifying not only the correlates of immunity present early after vaccination, but also those that persist in the host after the effector phase has ended. The maintenance of long-term protective immunity initiated by vaccination with F. tularensis strain 15 NIIEG has been shown to require the presence of antigen-specific CD4+ and CD8+ memory T cells producing IFNg and TNFa and expressing the activation marker CD69. A decrease in count and functional activity of CD8+TCM and CD8+TEM was detected in the long term after vaccination. The detected parameters of functional activity of memory T cells can be used as criteria for evaluation of protective immunity against virulent strains of F. tularensis.